THE ROLE OF SMALL-SCALE ENTREPRENEURSHIP IN INCREASING THE STANDARD OF LIVING OF THE POPULATION - Yu .P. Urunbaeva (Scholars Digest Publishing, 2023)
The article covers the relationship between small entrepreneurship and the standard of living of the population, theoretical and methodological problems of increasing the standard of living of the population in places, territorial aspects, and specific features of the development of the field of small and private entrepreneurship in the Republic of Uzbekistan. The growth of the share of small business and private entrepreneurship is devoted to the issues of expansion of the service sector, taking into account the modern requirements of filling the domestic market with quality and competitive goods, to the analysis of the position of this sector in the creation of new jobs, first of all, in the employment of young people and, on
Keywords: small business, private entrepreneurship, living standards of the population, social protection, employment, unemployment, innovation economy, market structure, new jobs, the income of the population.